O Conceito de Função do Contexto Universitário ao Contexto Escolar - Silva, Carla Renata Garcia Xavier da (2021)
The concept of function is treated in di erent ways depending on the context. However, the presentation of the concept is often vague. In this work, we bring a discussion about the concept of function and its properties in order to estabilish a formal and precise statement of a function de nition. We investigate the approaches of this concept in university and school contexts with the aim of verifying if the mathematical concept corresponds to the notion that is used at school. For this, we analyzed university texts and PNLD textbooks available on the internet and observed that language and notation abuses can distort this concept. As a result, we present the methodological foundations for teaching this concept from de subjects o ered in undergraduate courses.